Perilaku Tokoh Utama Ama Ola dalam Cerpen Kabar di Malam Natal Karya Silvester Petara Hurint (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
This study aims to describe the behavior of the main character Ama Ola in the short story "Kabar di Malam Natal" by SilvesterPetaraHurint. This study uses a qualitative method with analysis using psychoanalysis. The results of the study are as follows, (1) behavior that shows moral responsibility. The behavior of the main character Ama Ola that shows moral responsibility includes, a high attitude of responsibility, good morality, mutual trust, mutual protection, mutual respect, awareness to persist in a good and honorable attitude, and surrender and believe in the goodness and love of God, and (2) behavior that shows inner conflict. Behaviors that indicate inner conflict include loneliness, solitude, longing, warmth and assertiveness, courage towards oneself and anxiety, restlessness, fear that continues to rage and social dilemmas regarding the situation and circumstances around, obedience to the principles of life to maintain cultural, moral and religious customs.